Analisis Kebijakan Pemerintah Kota Blitar Dalam Mengembangkan Potensi Daerah Sebagai Upaya Meningkatkan Daya Saing Daerah - Dyah Elyta Kristiantina (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2013)
Abstract: Analysis of Government Policy of Blitar in Developing Region Potential For Improving Regional Competitiveness. Establishing policies of region potential development in order to improve competitiveness requires a clear insight about the potential of the region itself. Analysis tools used in this study are the Location Quotient (LQ) for determining the base and non-base sectors, shift share analysis (SSA) to determine region potential competitiveness, and policy advocacy using theory of sectoral policy approach. The analysis result shows that Blitar has the base sector namely trade and service sector, but has not had competitiveness, with the potential of tourism sector as a driver of the economy. . In the system of sectoral policies, policy advocacy for improving the competitiveness of the services and trade as a base sector can be done by developing non-base sector as the supporting sector, which is tourism sector. Development of the tourism sector activity can be done by increasing the number of tourist attractions based on the traditional, in this case is in line with the intention to build Blitar as national laboratories. Researchers contribute policy advocacy of